Alberto Magno en Los Andes : la escultura de Gerhard Marcks - Marcks, Gerhard, 1889-1981; Navas Sanz de Santamaría, Pablo, 1950- (Bogotá : Universidad de los Andes, Ediciones Uniandes, 2019)
'Albertus Magnus' is the best-known work of German sculptor Gerhard Marcks (Berlín, 1889 - Colonia, 1981). The bronze statue of saint Albert the Great located in the campus of the Universidad de los Andes and known as El Bobo' is one of the four replicas found in different parts of the world. "The book ... is a simple but important tribute that the University makes to this historic Uniandes symbol - as a sculpture, as a monument, as an emblem and as a badge - to remember its history, that of its author and that of the figure of Saint Albert Magnus. It is a modest contribution to the celebration of our 70 years of existence that we deliver to the Uniandes community so that we understand and appreciate more our beloved Bobo." (HKB Translation) --Verso Cover.
Introducción / Pablo Navas Sanz de Santamaría -- Discurso / Hernando Groot -- Alberto Magno y la tradición popular: entre el mago, el científico y el santo / Felipe Castañeda -- Gerhard Marcks / Heinz Ladendorf -- "El Bobo" en Los Andes / Claudia Montilla -- Saludo a Alberto Magno / Nicolás Vaughan.
En español.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Albertus, Magnus, -- Saint, -- 1193?-1280 -- Art; Marcks, Gerhard, -- 1889-1981.; Alberto Magno, -- Santo, -- 1193? -1280 -- Arte; Marcks, Gerhard, -- 1889-1981.; Universidad de los Andes (Colombia) -- History; Universidad de los Andes (Colombia) -- Historia; Christian saints in art; Santos cristianos En arte; Libros electrónicos.